WOMEN'S DECISIONS TO BE AN ENTREPRENEURSHIP IN THE INFORMAL SECTOR IN MAKASSAR - Karim, Kasnaeny; Jibril, Hadira Thumaninah (Faculty of Economics and Business, Hasanuddin University, 2019)
This study aims to determine the factors underlying women with high school education levels up to Bachelor, for entrepreneurship in the informal sector. Answer the research problem; the data were collected through 22 informants and then analyzed using a qualitative phenomenological approach. The results showed that six factors were underlying the decision of women to become entrepreneurs in the informal sector, which consisted of leisure time factors, Socio-cultural factors, Marriage factors, Ease factors, Capital Factors, and Economic Factors.